Gender Constructions in the Theological Dimension of the Sufi Premakhyans: Sufi Politics of Representation in the Citravali by Usman - Bocchetti, Annalisa (Religions of South Asia, 2021)
Through the analysis of the Citravali (1613 ce) by Usman, this article explores the interrelation between aesthetics, gender and religion within the Indian Sufi romances (premakhyans) in Avadhi language. These narratives reinterpret the Sufi semantics of love, narrating the quest of the hero in yogic disguise in search of the heroine, portrayed as a divine woman. Usman creatively reimagines the heroine of his romance as an artist, drawing on this motif to trace the allegory of creation as divine art. Therefore, this article identifies conventional aesthetic patterns in Usman’s narrative reproducing relevant gender dynamics, such as the eroticized and yet idealized image of the heroine in relation to the hero’s spiritual growth, contrasting with the escalation of the villain’s sexual desire. The traditional Hindu setting of the story broadly reflects the socio-cultural norms of the North Indian world in early modern times, and implies gender hierarchies established by the local society. The intersection of these points in the Citravali suggests further reflections on the articulation of gender in a rich branch of Sufi literature composed in a regional language of India, which may open new perspectives in the interpretation of the relationship between mysticism and eroticism.